2018
DOI: 10.1128/jcm.01653-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxacillin and Cefoxitin Disk Diffusion and MIC Breakpoints Established by the Clinical and Laboratory Standards Institute for Detection of mecA -Mediated Oxacillin Resistance in Staphylococcus schleiferi

Abstract: is a beta-hemolytic, coagulase-variable colonizer of small animals that can cause opportunistic infections in humans. In veterinary isolates, the rate of -mediated oxacillin resistance is significant, with reported resistance rates of>39%. The goal of this study was to evaluate oxacillin and cefoxitin disk diffusion (DD) and MIC breakpoints for detection of -mediated oxacillin resistance in 52 human and 38 veterinary isolates of Isolates were tested on multiple brands of commercial media and according to Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 37 publications
5
38
1
2
Order By: Relevance
“…Oxacillin BMD using CoNS breakpoints also yielded results that were highly accurate (with only one false-positive isolate), resulting in a ME rate of 2% and CA of 99%. While the zone of inhibition that was observed using Remel MHA was fainter than that observed using the other two brands, as previously described (8), the zone sizes were still readable and no notable differences in performance between all three brands were identified.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Oxacillin BMD using CoNS breakpoints also yielded results that were highly accurate (with only one false-positive isolate), resulting in a ME rate of 2% and CA of 99%. While the zone of inhibition that was observed using Remel MHA was fainter than that observed using the other two brands, as previously described (8), the zone sizes were still readable and no notable differences in performance between all three brands were identified.…”
Section: Discussionsupporting
confidence: 63%
“…Given the importance of accurate classification of methicillin resistance status, with the continued adoption of new technologies (e.g., matrix-assisted laser desorption ionization-time of flight mass spectrometry [MALDI-TOF MS]) by clinical laboratories that allow improved identification of staphylococci to the species level, there is a need to critically evaluate the best methods for detecting mecA-mediated oxacillin resistance in specific species of CoNS. The CLSI Staphylococcus Ad Hoc Working Group previously assessed the performance of phenotypic testing options for prediction of mecAmediated oxacillin resistance in Staphylococcus pseudintermedius and Staphylococcus schleiferi (8,9). This led to the discontinuation of cefoxitin disk diffusion (DD) testing and inclusion of oxacillin DD testing as an option for detecting mecA-mediated resistance in these species.…”
mentioning
confidence: 99%
“…In addition, a study examining atypical S. aureus isolates demonstrated a sensitivity of Ն90% and a specificity of 100% (11). However, limited data are available for non-SASS isolates, with the exception of recent work evaluating 54 S. schleiferi isolates, where the PBP2a SA culture colony test had a sensitivity and specificity of 100% (12). Therefore, we sought to determine the performance of the PBP2a SA culture colony test using a collection of 100 non-SASS isolates composed of 10 species obtained from animal and human subjects collected from four geographically distinct regions in the United States: Georgia (two distinct sites), Iowa, Missouri, and Texas.…”
mentioning
confidence: 99%
“…They also determined that cefoxitin disk diffusion or MIC methods should not be used as a surrogate for oxacillin methods, as they could not reliably detect mecA-mediated resistance in this species. In 2018, further studies suggested that the recommendations and breakpoints set for S. pseudintermedius were also ideal for the veterinary coagulasevariable species S. schleiferi (1). Furthermore, these studies found that cefoxitin disk diffusion should not be used as a method for confirming that non-S. epidermidis CoNS isolates from serious infections with oxacillin MICs in the 0.5-to-2.0-g/ml range are truly oxacillin resistant.…”
mentioning
confidence: 99%
“…Furthermore, these studies found that cefoxitin disk diffusion should not be used as a method for confirming that non-S. epidermidis CoNS isolates from serious infections with oxacillin MICs in the 0.5-to-2.0-g/ml range are truly oxacillin resistant. As such, laboratories should confirm the susceptibility of such isolates by mecA nucleic acid amplification test or PBP2a test (1,12).…”
mentioning
confidence: 99%